Safety of dapagliflozin initiation in acute decompensated heart failure patients with reduced left ventricular ejection fraction - Anastasiya E. Poskakalova; Svetlana N. Nasonova; Igor V. Zhirov; Sergey N. Tereshchenko (ZAO "Consilium Medicum", 2023)
Background. Chronic heart failure (CHF) is an immediate cardiological problem. At the same time, acute decompensated heart failure (ADHF) is associated with an extremely unfavorable prognosis and low survival of patients. Aim. To evaluate the safety of sodium-glucose cotransporter-2 inhibitor dapagliflozin early administration in patients with ADHF with a reduced left ventricular ejection fraction (LVEF) regardless of type 2 diabetes mellitus (diabetes). Materials and methods. We used standard CHF therapy and intravenous diuretic therapy in combination with 10 mg dapagliflozin in 43 patients with NYHA class IIIV ADHF. The study mainly included 39 (90.7%) male patients, the mean age was 6012 years (5663), diabetes was in 14 (32.6%) patients. Dapagliflozin was prescribed by a mean of 2 days (13) from admission to the hospital. The parameters were analyzed at the time of inclusion in the study and when CHF compensation was achieved. Results. The median of the length of hospital stay was 7 days (610). LVEF significantly increased during hospitalization from 276 to 307% (p0.001) and the level of NT-proBNP decreased: from 3700 pg/ml (17455331) to 1366 pg/ml (10252878); p=0.007. A decrease in the marker was observed in 90% of patients. Hypotension (decrease in systolic blood pressure BP less than 90 mmHg) was observed in 10 (23.3%) patients. A statistically significant decrease in BP was found: systolic and diastolic BP on admission was 114 mmHg (100126) and 70 mmHg (7080), respectively, when CHF compensation was achieved 110 mmHg (98120) and 70 mmHg (6178); p=0.047 and p=0.013, respectively. The increase in hematocrit during hospitalization was also statistically significant from 43.53.6 to 46.14.9% (p0.001) and this was found in 67% of patients. A total of 4 (9.3%) patients had acute renal injury (decrease in estimated glomerular filtration rate GFR by 25% or more). At the same time, there was no decrease in GFR of less than 15 ml/min/1.73 m2. There was no statistically significant decrease in GFR and an increase in creatinine levels during hospitalization (p=0.214 and 0.173, respectively). Urinary tract infections were observed in 1 (2.3%) patient, transient hypoglycemia in 2 (4.7%) patients, which did not lead to the discontinuation of dapagliflozin. Diabetic ketoacidosis, allergic reactions, syncope, lower extremity amputations were not observed in patients taking dapagliflozin. Conclusion. It can be concluded that dapagliflozin has a favorable safety profile when used in patients with ADHF, regardless of the presence or absence of diabetes.